Nursery Resource Pack Communication, Language and Literacy - Term I - The City School (Lahore : The City School)
Children learn to recognize letters, build vocabulary, and understand simple stories and rhymes. Activities include phonics, picture-word matching, and conversation practice to boost confidence. The pack encourages interactive, play-based learning to strengthen language and communication foundations.
Location: 1B
Keywords: Text- book